(untitled) (Información, cultura y sociedad, 2021)
Biblical and missionary societies began to distribute Protestant Bibles and texts in Spain on a regular basis in the 1830s, through agents. One of the most important of these agents was James Graydon. He operated in Barcelona, where he published the Nou Testament in Catalan (1836) and the Biblia (1837) in Spanish. Both works were printed at the workshop of Antonio Bergnes de las Casas, in addition to other polemic and apologetic Protestant, which the colporteur distributed throughout the Mediterranean coast. Bergnes’ network of agents and the role played by press advertising were essential for the distribution of these Protestant works. They were met by a notable response from Catholics, in newspapers and in anti-Protestant texts, which deepened the debate on religious freedom and the freedom of worship.